Physiologically Relevant Concentrations of Dolutegravir, Emtricitabine, and Efavirenz Induce Distinct Metabolic Alterations in HeLa Epithelial and BV2 Microglial Cells - George, Joseph W.; Mattingly, Jane E.; Roland, Nashanthea J.; Small, Cassandra M.; Lamberty, Benjamin G.; Fox, Howard S.; Stauch, Kelly L. (Frontiers in Immunology, 2021)
Microglia, the resident brain phagocytes, likely play a key role in human immunodeficiency virus (HIV) infection of the central nervous system (CNS) and subsequent neuropathogenesis; however, the nature of the infection-induced changes that yield damaging CNS effects and the stimuli that provoke microglial activation remains elusive, especially in the current era of using antiretroviral (ARV) drugs for ARV therapy (ART). Altered microglial metabolism can modulate cellular functionality and pathogenicity in neurological disease. While HIV infection itself alters brain energy metabolism, the effect of ARV drugs, particularly those currently used in treatment, on metabolism is understudied. Dolutegravir (DTG) and emtricitabine (FTC) combination, together with tenofovir (TAF or TDF), is one of the recommended first line treatments for HIV. Despite the relatively good tolerability and safety profile of FTC, a nucleoside reverse transcriptase inhibitor, and DTG, an integrase inhibitor, adverse side effects have been reported and highlight a need to understand off-target effects of these medications. We hypothesized that similar to previous ART regimen drugs, DTG and FTC side effects involve mitochondrial dysfunction. To increase detection of ARV-induced mitochondrial effects, highly glycolytic HeLa epithelial cells were forced to rely on oxidative phosphorylation by substituting galactose for glucose in the growth media. We assessed ATP levels, resazurin oxidation-reduction (REDOX), and mitochondrial membrane potential following 24-hour exposure (to approximate effects of one dose equivalent) to DTG, FTC, and efavirenz (EFV, a known mitotoxic ARV drug). Further, since microglia support productive HIV infection, act as latent HIV cellular reservoirs, and when dysfunctional likely contribute to HIV-associated neurocognitive disorders, the experiments were repeated using BV2 microglial cells. In HeLa cells, FTC decreased mitochondrial REDOX activity, while DTG, similar to EFV, impaired both mitochondrial ATP generation and REDOX activity. In contrast to HeLa cells, DTG increased cellular ATP generation and mitochondrial REDOX activity in BV2 cells. Bioenergetic analysis revealed that DTG, FTC, and EFV elevated BV2 cell mitochondrial respiration. DTG and FTC exposure induced distinct mitochondrial functional changes in HeLa and BV2 cells. These findings suggest cell type-specific metabolic changes may contribute to the toxic side effects of these ARV drugs.